Assessing the Entrepreneurial Inclination of Universiti Utara Malaysia MBA Students - Muhammad Safizal, Abdullah (2003)
This study investigated the entrepreneurial inclination of Universiti Utara Malaysia MBA studens. Specifically it aimed to investigated the relationships between entrepreneurial inclination and the demographic characteristis, namely gender, age, ethnicity, marital status and residence area of Universiti Utara Malaysia MBA studens. In order to carry out this research, a descriptive quantitative study was carried out. The units of analysis were the MBA students in Universiti Utara Malaysia main campus at Sintok, Kedah. Various MBA classes were selected using the Simple Random Sampling approach and all of the students from these selected classes became the respondents for this study. 189 respondents were managed to be included in the study. The questionnaires were distributed either by the researcher himself, through the lecturers of respective classes, or through researcher's friends who happened to be in the targeted classes. The respondents were given 15 minutes to attempt the questionnaire. The questionnaires were collected immediately after the respondents completed them. This technique of distribution yields a 100% of response rate and usable rate. The instrument used consisted of 2 parts; Part A and Part B. Part A was used for a demographic survey and Part B was used to measure the entrepreneurial inclination of the respondents. The latter part of the instrument was adopted from the Entrepreneurial Attitude Orientation Scale developed by Robinson (1991), the General Entrepreneurial Tendency developed by the Durham University Business School (1988) and Barcelona's (1992) survey.